2020
DOI: 10.1055/s-0040-1705178
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Derivatives for Kidney Protection in the Critically Ill Pediatric Population: A Systematic Review

Abstract: Different types of diuretics have been used to minimize fluid overload after resuscitation. This meta-analysis determined the effects of xanthine derivatives on creatinine, creatinine clearance, and urine output. Studies included data from pediatric patients, whoused theophylline or aminophylline, and included pre- and postxanthine data for at least one of the outcomes of interest. A total of 13 studies with 198 patients were included in the pooled analyses. The study recorded data prior, and a mean of 36 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Urine output increased by 3.36 mL/kg/h in the pooled analyses. 8 While the magnitude of change was not the same between the pooled analysis and the current study findings, the direction of change is the same. Creatinine also had the same direction of change in both studies, and in both studies, it trended toward significance but did not quite reach statistical significance.…”
Section: Discussioncontrasting
confidence: 50%
“…Urine output increased by 3.36 mL/kg/h in the pooled analyses. 8 While the magnitude of change was not the same between the pooled analysis and the current study findings, the direction of change is the same. Creatinine also had the same direction of change in both studies, and in both studies, it trended toward significance but did not quite reach statistical significance.…”
Section: Discussioncontrasting
confidence: 50%
“…12 Other individual studies after pediatric cardiac surgery have also demonstrated some beneficial effects of interventions such as fenoldopam, aminophylline, dexmedetomidine, and enhanced oxygen delivery either by reduction in the risk of AKI or by allowing for enhanced diuresis without worsening kidney function. 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30…”
Section: Discussionmentioning
confidence: 99%
“…All types of white blood cells have different defensive and protective functions, and timely and sufficient white blood cells are beneficial to defense against diseases. Xanthine is a derivative of purine that is frequently used as a mild stimulant and bronchodilator [ 31 ], especially for treating asthma symptoms [ 32 ]. In our results, adenine and xanthine have been proven to be at abnormal levels, which may lead to many health problems.…”
Section: Discussionmentioning
confidence: 99%